Expression pattern of genes involved in biomineralization in black and orange mantle tissues of pearl oyster, Pinctada persica - Parvizi, Fatemeh; Akbarzadeh, Arash; Farhadi, Ahmad; Arnaud-Haond, Sophie; Ranjbar, Mohammad Sharif (Frontiers in Marine Science, 2023)
A few species of mollusks display color variation in their soft tissues. In pearl oysters, the color polymorphism in mantle tissue is associated with the color and radiance of shell and pearl. The study of biomineralization related genes in mantle tissue of pearl oysters can be used as a suitable approach to better identify the molecular mechanisms that influence shell and pearl quality and color variations. In this study, we investigated the expression of biomineralization-related genes in black and orange mantle morphotypes of pearl oyster, Pinctada persica in both warm and cool seasons using quantitative real-time PCR. Our results showed that the genes involved in biomineralization of the prismatic and nacre layer, i.e.; ASP, KRMP, MRNP34, SHELL, SHEM1B, LINKINE, PIF, SHEM5, NACREIN, and in pigmentation (TYR2A) were significantly higher expressed in orange phenotype compared to those of black one. The higher expression of ASP, KRMP, SHEM5, LINKINE and NACREIN in orange phenotype was only observed in warm season, but PIF, SHELL, SHEM1B, and TYR2A were upregulated in both warm and cool seasons. These results suggest the existence of different genetic processes between the two color morphs of P. persica and the more active role of genes in orange morphotype, particularly in warmer season. This study provides better understanding of the molecular mechanisms underlying biomineralization in pearl oysters.